Real Effects of the Subprime Mortgage Crisis : Is it a Demand or a Finance Shock? - Tong, Hui.; Wei, Shang-Jin. (Washington, D.C. : International Monetary Fund, 2008)
We develop a methodology to study how the subprime crisis spills over to the real economy. Does it manifest itself primarily through reducing consumer demand or through tightening liquidity constraint on non-financial firms? Since most non-financial firms have much larger cash holding than before, they appear unlikely to face significant liquidity constraint. We propose a methodology to estimate these two channels of spillovers. We first propose an index of a firm's sensitivity to consumer demand, based on its response to the 9/11 shock in 2001. We then construct a separate firm-level index on financial constraint based on Whited and Wu (2006). We find that both channels are at work, but a tightened liquidity squeeze is economically more important than a reduced consumer spending in explaining cross firm differences in stock price declines.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet